Endothelial senescence is induced by phosphorylation and nuclear export of telomeric repeat binding factor 2–interacting protein - Kotla, Sivareddy (JCI Insight, 2019)
The interplay among signaling events for endothelial cell (EC) senescence, apoptosis, and activation and how these pathological conditions promote atherosclerosis in the area exposed to disturbed flow (d-flow) in concert remain unclear. The aim of this study was to determine whether telomeric repeat-binding factor 2–interacting protein (TERF2IP), a member of the shelterin complex at the telomere, can regulate EC senescence, apoptosis, and activation simultaneously, and if so, by what molecular mechanisms. We found that d-flow induced p90RSK and TERF2IP interaction in a p90RSK kinase activity–dependent manner. An in vitro kinase assay revealed that p90RSK directly phosphorylated TERF2IP at the serine 205 (S205) residue, and d-flow increased TERF2IP S205 phosphorylation as well as EC senescence, apoptosis, and activation by activating p90RSK. TERF2IP phosphorylation was crucial for nuclear export of the TERF2IP-TRF2 complex, which led to EC activation by cytosolic TERF2IP-mediated NF-κB activation and also to senescence and apoptosis of ECs by depleting TRF2 from the nucleus. Lastly, using EC-specific TERF2IP-knockout (TERF2IP-KO) mice, we found that the depletion of TERF2IP inhibited d-flow–induced EC senescence, apoptosis, and activation, as well as atherosclerotic plaque formation. These findings demonstrate that TERF2IP is an important molecular switch that simultaneously accelerates EC senescence, apoptosis, and activation by S205 phosphorylation.